The Therapeutic Effectiveness of Segmental Lung Resection Versus Lobectomy in Patients With Isolated Lung Metastases From Colorectal Cancer: Evidence From a Retrospective Cohort Study - Changhao Que; Qi Wang; Zhibo Ye; Peiyuan Lu; Chengfang Li; Dacheng Jin; Yaping Wang; Yunjiu Gou (International Journal of Clinical Practice)
Conclusions: Pulmonary segmentectomy offers superior advantages in terms of operative time, intraoperative blood loss, drainage volume on the first postoperative day, total postoperative drainage volume, and surgical costs.